Optimization of wind farm layout to maximize the energy yield - Bukurije Hoxha; Igor K. Shesho; Risto V. Filkoski (Energy Conversion and Management: X)
Over time, the use of wind turbines has evolved in terms of the size and number of the turbines. The change in wind turbines comes as a result of major structural changes and then an increase in their production capacity. In the framework of the most stable operation for the surface of the terrain used in this study, a series of configurations have been proposed that are directly related to technical and economic sustainability. The complete scenarios will be realized in Koznica, where one-year measurements are done. In the framework of the realized scenarios, it can be seen that there is variability in terms of energy output from these configurations, which maximally comes from wake losses caused by the terrain. In cases where the scenarios with the addition of small turbines are studied, they, in the technical aspect, affect the increase in energy production, which, if those turbines were not installed, would not be applied. As an important part, the economic aspect of the realization of the previous optimization scenarios is analyzed by using Monte-Carlo simulation for LCOE analysis. Thus, it can be concluded that the analyzed scenarios with the addition of small turbines in the optimization process are more suitable and feasible for implementation.